Molecularly Distinct Routes of Mitochondrial Ca(2+) Uptake Are Activated Depending on the Activity of the Sarco/Endoplasmic Reticulum Ca(2+) ATPase (SERCA) - Waldeck-Weiermair, Markus (American Society for Biochemistry and Molecular Biology, 2013)
The transfer of Ca(2+) across the inner mitochondrial membrane is an important physiological process linked to the regulation of metabolism, signal transduction, and cell death. While the definite molecular composition of mitochondrial Ca(2+) uptake sites remains unknown, several proteins of the inner mitochondrial membrane, that are likely to accomplish mitochondrial Ca(2+) fluxes, have been described: the novel uncoupling proteins 2 and 3, the leucine zipper-EF-hand containing transmembrane protein 1 and the mitochondrial calcium uniporter. It is unclear whether these proteins contribute to one unique mitochondrial Ca(2+) uptake pathway or establish distinct routes for mitochondrial Ca(2+) sequestration. In this study, we show that a modulation of Ca(2+) release from the endoplasmic reticulum by inhibition of the sarco/endoplasmatic reticulum ATPase modifies cytosolic Ca(2+) signals and consequently switches mitochondrial Ca(2+) uptake from an uncoupling protein 3- and mitochondrial calcium uniporter-dependent, but leucine zipper-EF-hand containing transmembrane protein 1-independent to a leucine zipper-EF-hand containing transmembrane protein 1- and mitochondrial calcium uniporter-mediated, but uncoupling protein 3-independent pathway. Thus, the activity of sarco/endoplasmatic reticulum ATPase is significant for the mode of mitochondrial Ca(2+) sequestration and determines which mitochondrial proteins might actually accomplish the transfer of Ca(2+) across the inner mitochondrial membrane. Moreover, our findings herein support the existence of distinct mitochondrial Ca(2+) uptake routes that might be essential to ensure an efficient ion transfer into mitochondria despite heterogeneous cytosolic Ca(2+) rises.